Kallmann syndrome - Xiang, Alexander; Ali, Shanzey (The Meducator, 2022)
Kallmann syndrome (KS) is a form of hypogonadotropic hypogonadism characterized by a combination of both an inability to smell and properly regulate hypothalamic gonadotropin-releasing hormone (GnRH) pulses. This, as a result, affects the release of follicle-stimulating hormone (FSH) and luteinizing hormone (LH) from the pituitary gland, which in turn influences the secretion of endocrine hormones, such as estrogen and progesterone. It is found fairly infrequently, at a rate of approximately 1 in every 125,000 females and 1 in every 30 000 males. The inability to regulate GnRH secretion from the hypothalamus leads to a variety of consequences, including reduced sex hormone levels and the delayed onset of puberty.